Smith's Nationalism Perspective in the Indonesian History Textbooks on The Youth Oath 1928 Narrative - Sari, Endah Puspita; Rizqi, Yoga Fernando (HISTORIKA, 2019)
This article discusses the nationalism contained in the 2013 revised edition 2nd year high school Indonesian history textbook in class XI semester 1, which is pursed on one subject (Youth Pledge). According to Anthony D. Smith, the purpose of this research is to see the view of nationalism in the material of youth oaths. This research method uses the approach of Anthony D's theory of nationalism, Smith. The results of research conducted indicate that the conditions of Indonesian society in 1928 had aspirations to unite even though under the pressure of Dutch colonialism. The Indonesian nationalism then gave birth to the youth oath, which contained unity, nationality, love of the motherland, and acknowledging the Indonesian people's identity. Thus the conditions in forming a nation in the view of Anthony D, Smith contained in the youth oath are appropriate.